Burnout, Work-Life Balance, and Employee ProductivityIn a Hybrid Work Environment: A Qualitative Study in Indonesia - Ratnasartika Aprilyani; Sri Ratnawati; Anna Mariani Kartasamita (CAKRAWALA : Management Science Journal, 2026)
The rapidly expanding hybrid work environment post-COVID-19 pandemic presents complex challenges for human resource management, particularly regarding burnout, work-life balance, and employee productivity. This study aims to thoroughly analyze how burnout and work-life boundary ambiguity affect employee productivity within Indonesia's hybrid work system. Employing a qualitative phenomenological approach through in-depth interviews, focus group discussions (FGD), and observation with 12 cross-sector informants, this research identifies four primary themes: (1) multidimensional burnout manifesting differently in hybrid contexts compared to traditional offices; (2) endemic work-life boundary ambiguity in hybrid arrangements; (3) contextual and non-linear productivity; and (4) the critical role of managerial support as a moderator. This study's novelty lies in conceptualizing the Hybrid Burnout Paradox, wherein hybrid work flexibility simultaneously reduces and exacerbates burnout depending on employees' psychological boundary quality. These findings challenge assumptions that hybrid flexibility inherently improves well-being, offering a new analytical framework relevant to HR practitioners and Indonesian employment policymakers. Practical implications include recommendations for hybrid policy development centered on structured autonomy, psychological boundary management training, and adaptive managerial role design.